WARTIME PROTECTION OF PREGNANT WOMEN WITH IMPAIRMENTS: A LEGAL AND HUMANITARIAN ANALYSIS - Uche Nnawulezi; Jacques Kabano; Obinna Nnanna Okereke; Faustin Nsanzimana (Fakultas Hukum Universitas Komputer Indonesia, 2026)
This paper investigates whether pregnant women with disabilities are adequately protected during warfare under the Convention on the Rights of Persons with Disabilities (CRPD), 2006. Using a comprehensive literature review, it evaluates intellectual works, opinion papers, and case law on rights-based protections for women with disabilities in wartime. The aim is to assess the adequacy of policy frameworks, guidelines, and practices in addressing heightened threats to pregnant women’s rights during conflicts. The review draws on global policy documents, journal articles, book chapters, and reports, offering suggestions for current and future safety strategies. Findings highlight the need to revise existing regulatory frameworks to ensure sustainable protections. The paper evaluates systematic action plans, assessing their relevance, suitability, and adequacy for sustainable maternity care for women with disabilities in wartime. It argues that, as vulnerable individuals, they require special safety measures. The paper recommends a specific convention or additional protocol to the CRPD to address their needs effectively. This study contributes to the discourse on protecting women with disabilities during wartime, emphasizing the importance of policy reforms and robust legislation for sustainable rights-based protections. Abstrak Makalah ini meneliti apakah perempuan hamil penyandang disabilitas mendapatkan perlindungan yang memadai selama konflik bersenjata berdasarkan Konvensi Hak-Hak Penyandang Disabilitas (CRPD) 2006. Melalui tinjauan pustaka komprehensif terhadap karya ilmiah, kerangka kebijakan, yurisprudensi, dan instrumen hukum humaniter internasional (IHL), penelitian ini mengevaluasi efektivitas kerangka perlindungan berbasis hak dalam menangani kerentanan interseksional yang dihadapi kelompok ini. Temuan menunjukkan adanya kesenjangan signifikan baik dalam CRPD maupun IHL terkait perlindungan khusus bagi perempuan hamil penyandang disabilitas. Risiko utama yang teridentifikasi meliputi keterbatasan akses terhadap layanan kesehatan reproduksi, peningkatan risiko terpapar kekerasan berbasis gender, serta hambatan dalam evakuasi yang aman. Makalah ini menganjurkan pengesahan protokol tambahan terhadap CRPD atau konvensi khusus untuk memastikan perlindungan yang berkelanjutan dan inklusif bagi penyandang disabilitas di masa perang. Selain itu, penelitian ini merekomendasikan adanya sinergi yang lebih kuat antara kerangka kerja CRPD, CEDAW, dan IHL. Studi ini berkontribusi pada diskursus mengenai respons kemanusiaan yang inklusif dan menyerukan reformasi kebijakan serta hukum yang mendesak.